Mathematics Student Worksheet Based on Guided Discovery for Concept Understanding and Curiosity - Depri Adelia; Raekha Azka (Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
This study aims to develop and produce a mathematics student worksheet based on guided discovery to facilitate the understanding concept and the curiosity of eighth grade students on prism and pyramid material. The type of research is research and development using the Richey and Klein development procedure, which consists of the planning, production, and evaluation. Mathematics student worksheet assessment for material and media experts. Material and media experts fill out the mathematics student worksheet assessment. The research data analysis technique is product quality analysis. According to the evaluation of material experts and media experts, the mathematics student worksheet is very good. Based on the results of the study, it found that the quality of the mathematics student worksheet based on guided discovery was classified as very good with the specification of the average score of the material expert validator assessment of 194.5 from the ideal maximum score of 208 and classified in the very good category with the specification of the average score of the media expert validator assessment of 57 from the ideal maximum score of 72. Based on this, the product of the guided discovery-based math worksheets is declared valid and can use in the learning process.